(3eSCdI aj GdcQGs - (3CHh GdbGSe, GdTQja GdeQJVi, Ydj Hf GdMSjf Hf ehSi, J (B436(3g` (B1044(3e(B)s ((3GdeTgO GdZQhejs)
(3ChdgG (B:s
(3gPg eSFdI (B... (3hgj EPG cGf GdePgH eSJbQG HCf eG HdZ ef GdejGg GdeMUhQI cQG de jfLSg TjA EdG eG ZjQ CMO ChUGag GdKdGKI, aeG Gdbhd aj eGFjf fLSjf ZjQ eJZjQjf jfbU cd hGMO efgG Yf GdcQ NdWG aHdZG cQGs
(3BNQgG (B:s
(3BNQgG(B: (3dhLH GdJhba aj GSJYeGd cd eG fLO ajg fLGSI de JZjQ ChUGag hEf cGf cKjQG dCfG dG fOQj cja MUhd gPg GdfLGSI ajg adeG de jcf HPdc GYJHGQ Od Ydi Cf GdCeQ Ydi eG PcQfGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B4: 278s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3abg GdePGgH GdCNQis